ANALYSIS OF WATER CARRYING CAPACITY BASED ON WATER QUALITY TO THE OPPORTUNITIES CULTIVATION ABALONE (Haliotis sp.) IN COASTAL KUTUH, BALI - Dewa Ayu Angga Pebriani; Ayu Putu Wiweka Krisna Dewi (Samakia : Jurnal Ilmu Perikanan, 2016)
The aim of this study was to determine the status of water quality that can be known whether or not the region's coastals Kutuh used as a location for the abalone aquaculture. This research was conducted in Kutuh coastal, Kutuh Village, District of South Kuta, Badung regency in August-September 2016. Data collection is done by carrying out measurements directly on the study site is in Kutuh coastal. Data of water quality was obtained from this research includes temperature, DO, pH, currents, salinity, ammonia and nitrite. The data were then analyzed using a quantitative descriptive excel program for windows. The range of water quality values measured show that the temperature, pH, salinity, and DO is still in the normal threshold. Values obtained ammonia and nitrite are very low and still within the normal threshold. Based on the results obtained, the water quality in the coastals Kutuh in good condition and can be used as a life medium for the abalone aquaculture.